A service research contribution to the global challenge of sustainability. Issue 5 (11th September 2017) - Saviano, Marialuisa; Barile, Sergio; Spohrer, James Clinton; Caputo, Francesco
Abstract : Purpose: Poverty, hunger, inequalities, diseases, unsustainable use of resources, etc., in spite of scientific progress, still remains unsolved worldwide issues. All these issues relate to the challenges of sustainability and sustainable development that now call for urgent answers. The purpose of this paper is to explore how the service research community can respond to this call and to identify key areas of potential contribution. Design/methodology/approach: After a brief review of selected service literature aimed at exploring its interest in the topics of sustainability and sustainable development, the authors develop the interpretative proposal identifying the key requirements of a global engagement in the challenge of sustainability and sustainable development and highlighting the potential contribution of service research. Findings: Findings highlight the potential contribution of service research to the global challenge of sustainability and suggest acting upon education by considering the "T-Shaped" professional model as a possible reference for embedding sustainability in the education of future managers and addressing the need of interdisciplinary thinking through the systems approach. Research limitations/implications: The proposed study of service literature is only an exploratory analysis of main contributions that does not aim to identify gaps but only to highlight the potential of a greater engagement of service research in the global call for a more sustainable and inclusive development. Practical implications: A trans-disciplinary approach is also required. This implies the involvement of the business and the social real world. Originality/value: This paper represents a novel call for engaging the service research community in a boundary-crossing collaboration with the aim of contributing to address the challenge of sustainability.